lncRNA CYTOR Facilitates Osteogenic Differentiation of Human Periodontal Ligament Stem Cells by Modulating SOX11 via Sponging miR-6512-3p - Shaoqin Tu; Yihua Chen; Yi Feng; Zhili Kuang; Yuxuan Wang; Lin Chen; Zhihui Mai; Jiaming Wei; Sai Zhang; Yiting Shao; Hong Ai; Zheng Chen (Stem Cells International)
Periodontal ligament stem cells (PDLSCs) are considered ideal cell sources for the regeneration of periodontal and alveolar bone tissue. Cytoskeleton Regulator RNA (CYTOR), a newly discovered long noncoding RNA, has been reported to function as competing endogenous RNA (ceRNA) and to be involved in many biological processes. However, its roles in PDLSC osteogenic differentiation remain unclear. Here, we firstly found CYTOR was mainly sublocalized in the cytoplasm of PDLSCs and CYTOR expression was increased during osteogenic differentiation of PDLSCs. By employing gain- and loss-of-function approaches, we then identified CYTOR overexpression promoted osteogenic differentiation of PDLSCs while CYTOR knockdown inhibited this process. Furthermore, bioinformatics analysis was utilized to show that both CYTOR and SOX11 mRNA contained the same seed sites for miR-6512-3p, which was further confirmed by dual luciferase reporter assay and RNA-binding protein immunoprecipitation. Notably, CYTOR conferred its functions by directly binding to miR-6512-3p and an inverse correlation between CYTOR and miR-6512-3p on the level on SOX11 and osteogenic differentiation of PDLSCs was obtained. Additionally, miR-6512-3p could bind to SOX11 mRNA 3′ UTR and repressed SOX11 expression. Moreover, level of SOX11 was significantly increased during osteogenic differentiation of PDLSCs. Knockdown of SOX11 attenuated the increasing effect of CYTOR overexpression on osteogenic differentiation of PDLSCs. Collectively, these data supported that CYTOR positively modulated the expression of SOX11 through competitively binding to miR-6512-3p, thus promoting osteogenic differentiation of PDLSCs. The CYTOR/miR-6512-3p/SOX11 axis could be a novel therapeutic target for periodontal regeneration medicine.